Relationship of chemical compositions with particleboard properties of pennisentum purpureum schumach - Phang,, Kep Yong (Universiti Malaysia Sarawak (UNIMAS), 2004)
Previous researches have shown that the plants (woody and non-woody) are rich in fibres and therefore are suitable as raw materials for producing value-added products. The goals of this study were to determine the chemical compositions of napier grass and to determine the correlation between the chemical compositions with the properties of particleboards produced from napier grass. Napier grass (Pennisetum purpureum Schumach.) was collected from Kuching area. They were chopped, flaked, grounded and air dried to a moisture content of 1013 %. The air dried grounded flakes were sieved between BS 40-60 mesh and used for chemical analysis. Particleboards (30 x 30 x 1) cm were fabricated with using sieved grass particle , 1 % hardener (NH4CI), 12 % resin to a targeted density of 800 kg/m3. The chemical analysis indicated the napier grass contained 77.21 % of holocellulose, 54.78% of aiphacelluJose, 28.79% of lignin, and 3.16% of ash. Particleboard properties for napier grass showed an internal bond, 0.69 NI mm2; bending strength (modulus of rupture), 24.25 NI mm 2; thickness swelling, 12.28 % and water absorption, 53.26 %. As a result of high percentages of holocellulose and lignin contained in napier grass, the bending strength and internal bond of particleboard produced met the lIS A 5908 classification for type 24-10 type (minimum 2 bending strength of24.0 NI mm 2 and minimum internal bond of 0.3 NI mm ) . Hot water and cold water bad positive correlation with internal bond and bending strength of particleboard due to the tannins and gum were able to protect the cellulose from fungus. Organic substances (waxes, resin, oils, and gum) of ethanol-acetone solubility were able to prevent the cellulose from fungus decay. Therefore, ethanol-acetone solubility was linearly correlated with internal bond and bending strength. The conclusion drawn from this study is the chemical com 'tions of napier grass has influence or relation on particleboard properties.